2007
DOI: 10.1134/s0006297907070127
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ganglioside GM3 biosynthesis in human monocyte/macrophages during culturing in vitro

Abstract: We found that GM3 levels in human peripheral blood monocytes and cultured monocyte-derived macrophages were 0.37 and 2.7 microg per million cells, respectively. GM3 synthase of monocytes and to a greater extent of monocyte-derived macrophages was shown to be able to sialylate endogenous substrate, lactosylceramide (LacCer), to form GM3. With exogenously added LacCer, GM3 synthase activity was 57.1 and 563 pmol/h per mg protein in monocytes and monocyte-derived macrophages, respectively. The revealed changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…GM3 synthase catalyzes the transfer of a sialic acid residue to the terminal galactose of lactosylceramide, resulting in the synthesis of the ganglioside, GM3, the common precursor to nearly all of the cellular gangliosides (Kolter et al 2002). In agreement with early observations that GM3 levels increase upon macrophage-like cell differentiation (Nojiri et al 1986), the expression of GM3 synthase is dramatically upregulated upon monocyte differentiation into macrophages (Gracheva et al 2007). TNF-α and other proinflammatory mediators are also associated with increased GM3 synthase gene transcription and expression levels (Tagami et al 2002; Blander et al 1999).…”
Section: 2 Glycosphingolipidssupporting
confidence: 91%
“…GM3 synthase catalyzes the transfer of a sialic acid residue to the terminal galactose of lactosylceramide, resulting in the synthesis of the ganglioside, GM3, the common precursor to nearly all of the cellular gangliosides (Kolter et al 2002). In agreement with early observations that GM3 levels increase upon macrophage-like cell differentiation (Nojiri et al 1986), the expression of GM3 synthase is dramatically upregulated upon monocyte differentiation into macrophages (Gracheva et al 2007). TNF-α and other proinflammatory mediators are also associated with increased GM3 synthase gene transcription and expression levels (Tagami et al 2002; Blander et al 1999).…”
Section: 2 Glycosphingolipidssupporting
confidence: 91%
“…Carbohydrate chains linked to glycoproteins and glycolipids are ligands to both bacterial and immune lectins such as selectins, galectins or 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 23 differentiation of human blood monocytes into macrophages 44 . Altogether, this strongly suggests that G M3 synthase may act as a metabolic bottleneck for the synthesis of the whole family of gangliosides, during monocyte-to-macrophage differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…GM3 is known to be present in the plasma membrane of macrophages and activated CD4 + T cells (20,24), the primary targets of HIV-1 and therefore the primary cells from which de novo virions are produced in vivo. It has been well established that chronic immune activation is a hallmark of HIV-1 disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although the previous assays demonstrated that modifications in the level of particle-associated GM3 or GM1 impacts the level of mDC capture, we sought to further verify this effect in a physiologically relevant cell type with naturally occurring differences in ganglioside levels. Whereas monocytes express a low level of membrane-associated GM3, this level is up-regulated either upon differentiation into macrophages (20) or upon immune activation (21). This dichotomy creates a tractable system wherein viruses are predicted to possess varying levels of GM3 when produced from differentially stimulated monocytes or macrophages.…”
Section: Liposome Model Of Virions Shows That the Inclusion Of α2-3-lmentioning
confidence: 99%